2007
DOI: 10.1029/2006jf000609
|View full text |Cite
|
Sign up to set email alerts
|

Velocity change of the Amery Ice Shelf, East Antarctica, during the period 1968–1999

Abstract: [1] Historic velocity measurements of Antarctica's ice sheet represent vital baseline values that allow ice flow velocity variations to be observed over multidecadal timescales, such as those due to climate change. Using velocity values derived from geodetic quality measurements made in the 1960s and from more recent GPS and remote sensing studies during the 1990s, we examine the variability of ice flow velocities of the northern Amery Ice Shelf, East Antarctica, over the 30-year period, 1968-1999. The histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 31 publications
2
31
0
Order By: Relevance
“…Our finding that the central AIS has not undergone substantial net surface elevation change over ∼39 years is consistent with the velocity change analysis of King et al [2007] who concluded that the central AIS had undergone only a very small reduction in ice velocity over the period 1968–1999. Simple considerations of force balance in the ice shelf suggest that a regionally slightly thinner ice shelf would be consistent with slightly lower velocities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that the central AIS has not undergone substantial net surface elevation change over ∼39 years is consistent with the velocity change analysis of King et al [2007] who concluded that the central AIS had undergone only a very small reduction in ice velocity over the period 1968–1999. Simple considerations of force balance in the ice shelf suggest that a regionally slightly thinner ice shelf would be consistent with slightly lower velocities.…”
Section: Discussionsupporting
confidence: 91%
“…Zwally et al [2005], for example, used ERS Radar Altimetry (RA) to show that many Antarctic ice shelves increased or decreased in elevation with typical rates of ±(0.1 -0.4) ma 1 over the period 1992-2001. [ 4 ]T he Amery Ice Shelf (AIS), East Antarctica (Figure 1), has along record of elevation measurements, acquired using various methods between 1968 and 2007. The first geodetic quality optical leveling profiles were obtained in late 1968 in conjunction with observations used to generate precise velocity and strain data [ Budd et al,1 982;King et al, 2007]. More than 500 km of the central AIS was surveyed along three profiles (two transverse and one longitudinal to the ice flow direction).…”
Section: Introductionmentioning
confidence: 99%
“…The negligible ice discharge change between 2000 and 2016 indicates the relatively stable dynamics of the AIS basin in recent decades. In fact, previous studies (King et al, 2007;Tong et al, 2018) have shown that the ice velocity in the AIS hardly changed in the past 45 years . An investigation of decade-scale ice-shelf thickness changes has also shown that the overall thickness change of the AIS is 1.6 ± 1.1 m per decade, which is close to zero (Paolo et al, 2015).…”
Section: Comparison Of the Ais Ice Discharge Estimates With Those Fromentioning
confidence: 92%
“…King et al (2007) established that a geographically correlated bias of between ±8 and 11 cm/day existed between the InSAR velocities of Joughin (2002) and Young and Hyland (2002) in comparison to the Terrestrial/GPS determined velocities in the AIS. Although this study was confined to the northern AIS, the identified error sources contributing to this bias, in particular the measured slant ranges, can be considered to be common to the entire RADARSAT solution.…”
Section: Comparison To Insarmentioning
confidence: 99%